A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMK TARUNA PEKANBARU IN REARRANGING SCRAMBLED SENTENCES INTO GOOD PARAGRAPHS - Fitri Indah Sari; Syofia Delfi; Masyhur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive research was aimed at finding out the ability of the second year students of SMK Taruna Pekanbaru in rearranging scrambled sentences into good paragraphs. This research focuses on students’ ability in rearranging scrambled sentences into good paragraphs based on rhetorical markers of constructing sentences. The data were collected using sentences-reordering test. The test contained 20items of scrambled sentences. The population were the second year students of SMK Taruna Pekanbaru that consist of 220 students. The sample size were 52 students who are from Class XI TAV and XI TSP chosen by using cluster sampling technique. The needed data were collected by giving written test that consist of 2 different of texts that posses different rhetorical markers. Based on the research, the data was found that students ability in rearranging scrambled sentences is in mediocre level of ability with the mean score was 60. According to this study, it is expected that teachers can use this type of test in the form of scrambled sentences to increase students’ ability in rearranging scrambled sentences into good paragraphs.Keywords : Ability, Scrambled Sentences, Paragraphs